INHIBITION OF HERPES SIMPLEX VIRUS BY SYNTHETIC DOUBLE-STRANDED RNA (POLYRIBOADENYLIC AND POLYRIBOURIDYLIC ACIDS AND POLYRIBOINOSINIC AND POLYRIBOCYTIDYLIC ACIDS) - Hamilton, L. D. (1969)
Two-stranded polyriboadenylic and polyribouridylic acids and polyriboinosinic and polyribocytidylic acids protect against herpes simplex virus-induced cytopathogenicity in HEp 2 cultures, systemic herpes simplex virus infection in mice, and herpes simplex virus-induced keratoconjunctivitis in rabbits.